Thermal properties of electrospun Poly(lactic acid) membranes - Sencadas, Vítor João Gomes Silva (2012)
In the present work, PLA electrospun membranes were processed by electrospinning and characterized by electron scanning microscopy and thermal analysis. The polymer membrane showed a random fiber distribution with a mean diameter of 1 μm (± 300 nm). Differential scanning calorimetry experiments showed that the membrane has a glass transition, cold crystallization and melting temperatures of 54, 90 and 151 ºC, respectively. The kinetic study of thermal degradation of PLA under a nitrogen atmosphere was performed by means of thermogravimetry (TGA). It was found that the thermal decomposition kinetics of PLA can be interpreted in terms of a multi-step degradation mechanism. Several theoretical models were applied to the TGA data. The activation energies obtained by the Broido and Ozawa-Flynn-Wall models are in good agreement with the value of the activation energy calculated by 2 the Kissinger method. The activation energies of PLA calculated by the three methods were 176, 148 and 157 kJ.mol-1, respectively, similar to the values observed in PLA films.